The Clinical and Cellular Impact of RBMS2 on the Progression and Prognosis of Kidney Renal Clear Cell Carcinoma - Zhixiang Gao; Shouren Fan (Genetics Research)
This research delves into the implications of the RNA binding motif, single stranded interacting protein 2 (RBMS2)—a gene associated with tumor-suppressing functions—in the context of kidney renal clear cell carcinoma (ccRCC). Through meticulous exploration of online databases, we have identified a negative association between RBMS2 expression and adverse clinico-pathological features, such as advanced TNM stage. Furthermore, our findings indicate that RBMS2 acts as a prognostic predictor for clinical outcomes in ccRCC, evidenced by both univariate and multivariate analyses. Cellular assays have corroborated these findings, revealing that an overexpression of RBMS2 curtails ccRCC cell proliferation and migration. Additionally, our research has unearthed links between RBMS2 and immune infiltration within the ccRCC tumor microenvironment. Collectively, our results underscore the tumor-inhibiting role of RBMS2 in ccRCC and spotlight its potential as a prognostic marker and therapeutic intervention target.